The Optical Characteristics of 20 Watt Far-UVC Light and Its Application for Disinfection Chamber - Nidya Chitraningrum; Yusuf Nur Wijayanto; Hana Arisesa; Indra Sakti; Dadin Mahmudin; Budi Prawara; Deni Permana Kurniadi; Pamungkas Daud (Jurnal Elektronika dan Telekomunikasi, 2022)
The far-ultraviolet C (UVC) light has been used recently as an alternative disinfection system to deactivate the novel coronaviruses that cause coronavirus disease (COVID-19) without introducing any health damage to humans. We investigate that the far-UVC light from far-UVC excimer lamps (BEST 20 Watt) is a promising candidate for a far-UVC disinfection system to prevent human-to-human transmission of COVID-19. The optical characterization of far-UVC excimer lamps was examined. The maximum irradiance of the far-UVC excimer lamps is 219 nm, which is known to have antimicrobial capabilities on microorganisms, including coronaviruses. We propose a design of a disinfection chamber system based on eight 219 nm far-UVC excimer lamps which are attached vertically about 35 cm to each other, and the irradiation angle was installed at the angle of approximately 120° in order to optimize the irradiation of far-UVC light to a human body. For microorganism inactivation at a distance of around 10 cm from the human body, 219 nm far-UVC excimer lamps requires less than 5 s of irradiation time and the required intensity of 840 mW/cm2 at a low dose of 3000 mJ/cm2. We recommend that our proposed disinfection chamber can be used for humans and applied in public areas to decrease the spread of COVID-19 without any adverse health effect.